PENGEMBANGAN MEDIA FILM KARTUN BERBAHASA JAWA UNTUK PEMBELAJARAN BERDIALOG SISWA KELAS X SMA DI BANYUMAS - Witriningrum, Sri Galuh; Kurniati, Endang; Sukoyo, Joko (Jurnal Penelitian Pendidikan, 2017)
This purpose of this research aims to develop the media dialouge using wangsalan/parikan by utilizing the Javanese cartoon move as the mdia in accordance with Javanese manners. The study design is Research and Development (RD). The research used questionnaire of teacher and action test. The analysis of data is using qualitative descriptive analysis. The result of dvelopment Javanese cartoon movie as a media is adequate, effective, and material has also been good.